Association between waist circumference and chronic pain: insights from observational study and two-sample Mendelian randomization - Xu, Ting; Jin, Fan; Yu, Yeting; He, Jie; Yang, Ren; Lv, Tian; Yan, Zhangjun (Frontiers in Nutrition, 2024)
Background: Current research offers limited clarity on the correlation between waist circumference and chronic pain prevalence. Objective: This investigation seeks to elucidate the potential relationship between waist circumference and chronic pain and their causal association. Methods: An observational study was conducted, leveraging data from the National Health and Nutrition Examination Survey (NHANES) collected between 2001 and 2004. The multivariable logistic regression was used to assess the relationship between waist circumference and chronic pain. Furthermore, a meta-analysis of Mendelian Randomization (MR) was applied to explore a causal relationship between waist circumference and pain. Results: The observational study, post multivariable adjustment, indicated that an increase in waist circumference by 1 dm(decimeter) correlates with a 14% elevation in chronic pain risk (Odds Ratio [OR] = 1.14, 95% Confidence Interval [CI]: 1.04-1.24, P = 0.01). Moreover, the meta-analysis of MR demonstrated that an increased waist circumference was associated with a genetic predisposition to pain risk (OR=1.14, 95%CI: 1.06-1.23, P=0.0007). Conclusion: Observational analysis confirmed a significant relationship between increased waist circumference and the incidence of chronic pain, and results based on MR Study identified increased waist circumference as potentially causal for pain.